Quince días largos: la pandemia en una comunidad terapéutica para usuarios de drogas en Lambayeque (2020-2021) - Caycay Carpio, Renzo Josue (Pontificia Universidad Católica del Perú, 2021)
The lack of mental health care in Lambayeque has motivated the creation of informal projects for the rehabilitation and punishment of drug use in young people. This research seeks to understand how the program of a therapeutic community is assembled with the logic of medical immunity during the COVID-19 pandemic. The latter had consequences on the health and economy of families, which reduce the financial capacity of rehabilitation projects. Based on an ethnographic work and the narratives of five inmates about their first fifteen days of quarantine in the establishment, we show that, far from representing an organizational limitation, the pandemic consolidates the disciplinary procedures of this and other punitive, clinical, and mental complexes. Compared with the known situation, the new modality of preventive reception of the disease is functional to the programming process that turns the individual into an object susceptible to reformulation and transformation.

La falta de atención en salud mental en Lambayeque ha motivado la creación de proyectos informales de rehabilitación y sanción del uso de drogas en jóvenes. La presente investigación busca comprender cómo se ensambla el programa de una comunidad terapéutica con la lógica de la inmunidad médica durante la pandemia de la COVID-19. Esta última trajo consecuencias sobre la salud y economía de las familias, que reducen la capacidad financiera de los proyectos de rehabilitación. A partir de un trabajo etnográfico y de narraciones de cinco internos sobre sus primeros quince días de cuarentena en el establecimiento, mostramos que, lejos de representar una limitación organizativa, la pandemia consolida los procedimientos disciplinarios de este y otros complejos punitivos, clínicos y mentales. En comparación con la situación conocida, la nueva modalidad de recepción preventiva de la enfermedad resulta funcional al proceso de programación que convierte al individuo en un objeto susceptible de reformulación y transformación.
Fifteen long days: the pandemic in a therapeutic community for drug users in Lambayeque
Keywords: Comunidades terapéuticas; Usuarios de drogas; Pandemia; Disciplina; Violencia informal; https://purl.org/pe-repo/ocde/ford#5.04.01